Human resource management in virtual organizations - Heneman, Robert L.; Greenberger, David B. (Research in human resource management., 2002)
Sections covered in this book include: defining virtual organizations and implications for human resource management; outsourcing human resources; job analysis and competency assessment; training and development; performance management; compensation; and negotiations.